2015
DOI: 10.1088/0004-637x/807/2/139
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICAL PROPERTIES OF COMPACT STAR-FORMING GALAXIES ATz∼ 2–3

Abstract: We present a study on the physical properties of compact star-forming galaxies (cSFGs) with M * ≥ 10 10 M ⊙ and 2 ≤ z ≤ 3 in the COSMOS and GOODS-S fields. We find that massive cSFGs have a comoving number density of (1.0 ± 0.1) × 10 −4 Mpc −3 . The cSFGs are distributed at nearly the same locus on the main sequence as extended star-forming galaxies (eSFGs) and dominate the high-mass end. On the rest-frame U −V vs. V − J and U − B vs. M B diagrams, cSFGs are mainly distributed at the middle of eSFGs and compac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 69 publications
3
49
0
Order By: Relevance
“…It is clear that the fraction of these cSFGs decrease with redshift, which is a strong evidence that some of these cSFGs are translating into cQGs. It is reported in Fang et al (2015) that cSFGs also have slightly lower SFRs than eSFGs at 2 < z < 3 . It supports that the overall star-forming status for cSFGs are turning down with the decrease of redshift, which implies that the cSFGs at the lower redshift are more likely to be quenched.…”
Section: The Sfr−m * Relationmentioning
confidence: 84%
“…It is clear that the fraction of these cSFGs decrease with redshift, which is a strong evidence that some of these cSFGs are translating into cQGs. It is reported in Fang et al (2015) that cSFGs also have slightly lower SFRs than eSFGs at 2 < z < 3 . It supports that the overall star-forming status for cSFGs are turning down with the decrease of redshift, which implies that the cSFGs at the lower redshift are more likely to be quenched.…”
Section: The Sfr−m * Relationmentioning
confidence: 84%
“…These include the compact SFGs (cSFGs) at z 2 to z ∼ 4 (e.g. Barro et al 2013;Patel et al 2013;Stefanon et al 2013;Barro et al 2014;Fang et al 2015;van Dokkum et al 2015;Spilker et al 2016), and the passive, V JL selected galaxies at z = 2.5 − 4, which tend to be disk-dominated (Fan et al 2013). Toft et al (2014) speculated that the Barro et al (2013) cSFGs at z 3 might represent a transition phase between some of the z 3 SMGs and z ∼ 2 cQGs.…”
Section: Comparison Of the Physical Properties Between Different Galamentioning
confidence: 99%
“…Of course, morphological disturbance above the main sequence is not universal; see Barro et al (2016)). 3) Compact star-forming galaxies (cSFGs, as defined in Barro et al (2013)) on or just below the main sequence at z∼ 2-3 suggest that bulge growth precedes quenching (Barro et al 2014;Williams et al 2014;Fang et al 2015). Fang et al (2015) even found that at z∼ 2-3, cSFGs dominate the high mass end of the main sequence.…”
mentioning
confidence: 99%
“…3) Compact star-forming galaxies (cSFGs, as defined in Barro et al (2013)) on or just below the main sequence at z∼ 2-3 suggest that bulge growth precedes quenching (Barro et al 2014;Williams et al 2014;Fang et al 2015). Fang et al (2015) even found that at z∼ 2-3, cSFGs dominate the high mass end of the main sequence. 4) Quiescence is almost always associated with a bulge component or high central stellar mass density or velocity dispersion (Franx et al 2008;Bell et al 2012;Wake et al 2012;Fang et al 2013;Bluck et al 2014;Lang et al 2014;Woo et al 2015;Teimoorinia et al 2016).…”
mentioning
confidence: 99%